Determinants of Willingness to pay for Employment-Based Health Insurance Among Governmental School Workers in Saudi Arabia - Nouf Sahal Alharbi PhD (SAGE Publishing, 2021)
School workers constitute the bulk of public workers in Saudi Arabia. Most of these workers seek public health care services through the Ministry of Health, which is characterised by an overloaded service. Consequently, the government is planning to introduce employment-based health insurance. However, government employees' willingness to pay (WTP) for health insurance was not investigated. This study explores the feasibility and acceptability of employment-based health insurance by examining public school workers' WTP. Methods: six hundred and twenty-second number participants from Riyadh city were interviewed from September to October 2020 using an online structured questionnaire. The contingent valuation method with a payment card was used to assess WTP among the participants. This study also determined the association between the willingness to participate and WTP for health insurance respondents' demographic and socio-economic characteristics. Chi-square and multiple linear regression analyses were used to analyse the data. The majority (76%) with an average monthly mean of 77.9 Saudi Riyal (SAR) ($20.7) per capita. Male, had higher educated, and those diagnosed with chronic disease were more likely to report a willingness to participate and/or pay for health insurance ( P > .005). This study demonstrates that WTP for employment-based health insurance depends on workers' characteristics. The results of this study may be of use to policymakers to help with a set insurance premium, priority setting and fund allocation.